2012
DOI: 10.9799/ksfan.2012.25.1.105
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Dietary Habit and Eating Snack Behaviors of Middle School Students with Different Obesity Indexes in Chungnam Area

Abstract: The purpose of this study was to investigate the dietary habits and snack consumption behaviors of middle school students with different obesity indexes in the Chungnam area. The survey was carried out using self-questionnaires and included 385 students (119 underweight, 193 normal weight, 66 overweight). The rate of skipping meals was higher for underweight students than overweight students; however, this difference was not statistically significant. The mean time of meal was 10 to 20 minutes and the criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…A systematic review of 16 studies by Szajewska and Ruszczynski demonstrated that eating breakfast has a protective effect against overweight/obesity (13 studies, 81.25%). However, no significant difference was observed in this association, in some studies . In a study, which focused on nutritional status with regards to the consumption of breakfast among the youth, it was found that those who ate breakfast had a varied food intake, high intakes of vegetables and proteins, and significantly lower fasting blood glucose levels compared to those who did not eat breakfast .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A systematic review of 16 studies by Szajewska and Ruszczynski demonstrated that eating breakfast has a protective effect against overweight/obesity (13 studies, 81.25%). However, no significant difference was observed in this association, in some studies . In a study, which focused on nutritional status with regards to the consumption of breakfast among the youth, it was found that those who ate breakfast had a varied food intake, high intakes of vegetables and proteins, and significantly lower fasting blood glucose levels compared to those who did not eat breakfast .…”
Section: Discussionmentioning
confidence: 96%
“…However, no significant difference was observed in this association, in some studies. 26,27 In a study, which focused on nutritional status with regards to the consumption of breakfast among the youth, it was found that those who ate breakfast had a varied food intake, high intakes of vegetables and proteins, and significantly lower fasting blood glucose levels compared to those who did not eat breakfast. 28 These studies show that, although skipping breakfast is not a direct cause of obesity, it causes youths' nutritional quality to suffer and leads to an increase in highcalorie snacking; therefore, it is suggested that regular breakfast consumption can decrease the risk of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…신체적 성장이 급속도로 일어나는 시기인 청소년기는 영 양과 수면이 평생의 건강과 밀접한 관련을 갖게 되므로 (5,6) 이들의 식생활 및 간식섭취 행동 (7)(8)(9), 수면상태에 대하여 많은 관심이 집중되고 있다 (10)(11)(12). 그중에서도 시간적으로 제약을 많이 받는 중․고등학생들의 경우에는 과열된 교육환 경으로 인해 운동시간이 감소하고 있으며 (13), 빠른 등교와 늦은 귀가로 인한 아침결식, 식사시간의 불규칙성, 간식 및 외식 빈도의 증가 (14), 수면부족 등으로 안정된 식사와 수면 을 취하기가 어렵다.…”
Section: 서 론unclassified